The Influence of Financial Literacy, Family Financial Education, and Financial Behavior on Borrowing Intention from Online Loans/P2P Lending among University Students in Manado - Henry Daniel Pateh; William Tjong (Universitas Pelita Harapan, 2025)
This study examines the influence of financial literacy, family financial education, and financial behavior on the intention to borrow from online loans/P2P Lending among university students in Manado. Using a quantitative associative approach, data were collected from 100 respondents through an online questionnaire and analyzed with Partial Least Square – Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy significantly influences borrowing intention, while family financial education does not significantly affect either borrowing intention or financial behavior. Moreover, financial behavior does not mediate the relationship between financial literacy or family financial education and borrowing intention. These results emphasize the importance of financial literacy in shaping students’ financial decision-making, while suggesting that family-based financial education alone may not be sufficient. This study contributes to financial literacy and fintech borrowing literature, offering insights for policymakers, universities, and fintech providers to promote responsible borrowing behavior among students